The authority of the Buddha: The limits of knowledge in medieval Indian Buddhist epistemology - Payne, Richard (Acta Orientalia Vilnensia, 2010)
Institute of Buddhist Studies at the Graduate Theological Union The Indian religious traditions, including Buddhism, are generally characterised by an understanding of the problematic character of the human condition as ignorance (avidya) instead of sin, as in Christianity.1 The centrality of ignorance in defining the problematic character of the human condition creates a dramatically different religious dynamic—a religious dynamic that is fundamentally concerned with epistemological issues rather than with moral ones. In Indian discussions of the limits of religious knowledge, the shared intellectual framework was the idea of means of valid knowledge (pramāṇa). While other religio-philosophic traditions in India accepted testimony (śabda) as an autonomous (i.e., irreducible) means of valid knowledge, Buddhist epistemologists rejected it. Having rejected the idea that testimony is an autonomous means of valid knowledge (śabdapramāṇa), an alternative explanation for the authority of the Buddha had to be created. Against this background of epistemological discussion, particular attention is given here to Dharmakīrti’s views on the authority of the Buddha as a means of valid knowledge regarding the ground of human existence, the path of religious practice, and the goal of awakening.